Urinary Level of CA19-9 as a Tumor Marker in Urothelial Carcinoma of the Bladder - Pal, Keya; Roy, Suparna; Mondal, Samim Ali; Chatterjee, Uttara; Tiwari, Punit; Bera, Malay (Urology Journal, 2011)
Purpose: To diagnose the urothelial carcinoma of the bladder by measuring CA19-9 level in the urine. Materials and Methods: This study was conducted on 47 patients with histopathologically confirmed urothelial cancer and 50 control subjects. The urinary level of CA19-9 was measured in both groups by enzyme-linked immunosorbent assay after concentration of urine with Bio-Gel dry beads. Urine cytology was also done in both controls and patients. Results: The mean urinary level of CA19-9 was 194.59 ± 110.56 u/mL in patients and 11.67 ± 8.42 u/mL in controls (P = .0001). The mean urinary level of CA19-9 in patients with low-grade and high-grade bladder cancer was 206.56 ± 114.56 u/mL and 174.80 ± 94.06 u/mL, respectively (P = .56). Urine cytology by Papanicolaou stain was mostly negative. Conclusion: It can be concluded that CA19-9 may be a useful non-invasive test to diagnose the urothelial carcinoma of the bladder.